2018
DOI: 10.1108/ijhcqa-09-2016-0122
|View full text |Cite
|
Sign up to set email alerts
|

Fall prevention strategy in an emergency department

Abstract: Purpose The purpose of this paper is to document the need for implementing a fall prevention strategy in an emergency department (ED). The paper also spells out the research process that led to approving an assessment tool for use in hospital outpatient services. Design/methodology/approach The fall risk assessment tool was based on the Morse Fall Scale. Gender mix and age above 65 and 80 years were assessed on six risk assessment variables using χ analyses. A logistic regression analysis and model were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
2
0
4
Order By: Relevance
“…According to the assessment with the MEDFRAT, 33.3% of Portuguese users had a risk of falling, with 18.8% being low risk, 7.5% moderate risk and 7% high risk, values lower than those found in other studies [ 25 , 26 ] and similar to those found by Southerland et al [ 27 ]. The fact that our sample had a fall risk of 31.7% and in Scott et al’s [ 25 ] study the fall risk was 53% makes us wonder why there is such a difference.…”
Section: Discussionsupporting
confidence: 58%
“…According to the assessment with the MEDFRAT, 33.3% of Portuguese users had a risk of falling, with 18.8% being low risk, 7.5% moderate risk and 7% high risk, values lower than those found in other studies [ 25 , 26 ] and similar to those found by Southerland et al [ 27 ]. The fact that our sample had a fall risk of 31.7% and in Scott et al’s [ 25 ] study the fall risk was 53% makes us wonder why there is such a difference.…”
Section: Discussionsupporting
confidence: 58%
“…Esta pesquisa seguiu os preceitos da ética em pesquisa com seres humanos, segundo as Resoluções nº466/12 e nº510/ 16 qual mostrou que 53,33% dos pacientes avaliados pela escala de Morse apresentaram alto risco de queda. 10 Ao considerar a criticidade e especificidade do atendimento realizado aos usuários em UPA, estratificar o risco de queda no momento da triagem clínica, ou em outro momento oportuno, torna-se importante para direcionar e sistematizar ações multifatoriais que impactem na prevenção de quedas e lesões decorrentes destas aos usuários do serviço, reduzindo custos desnecessários 16 e contribuindo com a segurança e a qualidade do cuidado prestado nesta importante modalidade de assistência não hospitalar.…”
Section: Métodounclassified
“…Esses resultados são semelhantes ao estudo conduzido com pacientes adultos hospitalizados em hospital privado da região sul do Brasil que verificou associação entre idade (idoso e não idoso) e risco de queda (p<0,001),17, bem como investigação realizada no Canadá a qual apontou risco de queda em 5.371 (56,5%) pacientes geriátricos. 16 Entretanto, o inverso foi encontrado em um estudo observacional, o qual identificou que os pacientes sob o risco de queda no departamento de emergência eram adultos jovens, em uso de álcool ou de outras substâncias ilícitas. 18 Essas divergências estão relacionadas aos múltiplos fatores de riscos intrínsecos (relacionados ao paciente) e extrínsecos (condições ambientais e organizacionais) de queda, 19 somados ao perfil demográfico, tecnológico e epidemiológico distintos entre as mais variadas regiões geográficas, bem como dos determinantes sociais de saúde de cada população em âmbito mundial e nacional.…”
Section: Métodounclassified
“…The MSF is a widely used tool in geriatric care worldwide, and it has been recommended by the US VA National Center for Patient Safety for use as a screening tool (Muray et al, 2018). In the past, the MFS was not commonly used in Israel.…”
Section: Review Of the Literaturementioning
confidence: 99%